Tumoral calcinosis: a manifestation of extreme metastatic calcification occurring with 1, alpha-hydroxycholecalciferol therapy. Issue 623 (September 1977) - Walker, G. S.; Davison, A. M.; Peacock, M.; McLachlan, M. S.
Abstract : Two cases are reviewed, both of which developed tumoral calcinosis whilst receiving 1, alpha-hydroxy-cholecalciferol therapy. Tumoral calcinosis is an extreme form of peri-articular calcification, and its occurrence in patients with chronic renal failure is unusual. These peri-articular masses developed around the shoulders in both patients, and the action of 1, alpha-hydroxycholecalciferol as a possible factor promoting this form of metastatic calcification is discussed.